Produksi Bioetanol Dari Reject Of Stock Preparation Pada Proses Pembuatan Kertas Dengan Proses Hidrolisis Dan Fermentasi - Sitinjak, Jufri Suanto; Chairul, Chairul; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indonesia is one of the largest paper producing and exporting countries in the world. Along with the increase in paper production, solid waste is generated from the reject of stock preparation. These reject of stock preparation has the potential to produce bioethanol because it contains a high cellulose content of 85,53% and hemicellulose 3,88% which is able to support the provision of renewable and environmental friendly fuels. The purpose of this study was to obtain the concentration of sulfuric acid (H2SO4) and hydrolysis temperature that can produce the highest sugar concentration in the reject of stock preparation hydrolysis process into sugar; to get the best pH value and fermentation time in the fermentation process by using Saccharomyces cerevisiae; and also get the percent yield of fermented sugar into bioethanol. The stages in this research is pretreatment of samples refined with a 1000 micron sieve (18 mesh), then the hydrolysis process with various concentrations of sulfuric acid (H2SO4) 6, 8, 10, 12% (v/v) and temperatures of 120oC, 130oC and 140oC for 30 minutes. Finally, the fermentation process was carried out with a variation of pH 4.5; 5; and 5,5 and fermentation time of 24, 48, 72 and 96 time. Based on the research results, the highest total sugar concentration of 9,8244 g/l was obtained in the hydrolysis process with a concentration of 12% (v/v) H2SO4 and a temperature of 140oC. The highest bioethanol concentration of 5.83 g/l was obtained in the fermentation process with the best pH 4.5 and fermentation time of 72 hours with the percent yield obtained at 85.88% (0.44 gram bioethanol / gram sugar). Keywords : Bioethanol, fermentation, hydrolysis, reject of stock preparation, Saccharomyces cerevisiae